World uncertainty and national fiscal balances - Trang Thi Thuy Nguyen; Binh Thai Pham; Hector Sala (Journal of Applied Economics, 2023)
The Great Recession and the COVID-19 pandemic shared two of its critical macroeconomic consequences: a major increase in world uncertainty and great stress on public finances. In this paper, we show that not only these are not independent phenomena but, on the contrary, world economic uncertainties are relevant in determining country-specific fiscal balances. We provide consistent evidence for 143 countries over the period 1990-2019 that the former harms fiscal balances irrespective of the degree of economic development. In this way, an increase of 0.1 points in the world uncertainty index triggers, on average, 0.15 GDP percentage points deterioration in the fiscal balance. This average value is subject to significant non-linearities characterized by larger negative effects the higher the fiscal balance is. In a critical period in which public debts have climbed to unprecedented historical levels, economic stability appears as a non-negligible factor in the forthcoming process of public accounts rebalancing.
Keywords: 330; (un)conditional quantile regression; fiscal balance; public deficit; Uncertainty